DAMPAK LINGKUNGAN KERJA TERHADAP MOTIVASI DAN TURNOVER INTENTION KARYAWAN PADA INDUSTRI GARMEN DI KABUPATEN TANGERANG - Nurhalim, Andres Dharma (Jurnal Nusa Manajemen, 2024)
Indonesia is one of the largest garment producing countries in the world. However, research shows that garment companies in Indonesia have high turnover rates and above the average turnover rate in all industries. Therefore, this research explores the impact of the work environment on employee motivation and turnover in the Indonesian garment industry. This research is qualitative research. Data collection was carried out face to face. face interviews with 16 participants from two garment companies in Tangerang Regency, PT. ABC and PT. XYZ. Meanwhile, data analysis was carried out using thematic analysis. From the interview results, it is known that the physical and non-physical work environment is an important aspect and has an influence on employee motivation and turnover at PT. ABC and PT. XYZ. The physical and non-physical work environment is included in Herzberg's theoretical factors, which if these factors are met, job dissatisfaction can be reduced. This increases employee motivation to complete work, feel comfortable at work, and have no intention of leaving. Maintaining a good physical and non-physical work environment is very important for both companies because it can affect employee motivation and turnover.